1900
DOI: 10.1007/bf01662541
|View full text |Cite
|
Sign up to set email alerts
|

Ueber den Einfluss minimaler Mengen Nebennierenextracts auf den arteriellen Blutdruck

Abstract: Nachfolgende Untersuchungen sind zuniichst unternommen worden, um die geringste Menge b~ebennierenextracts zu finden, welche noch eine deutliche BlutdruckerhShung hervorruft. Solch eine Beobachtung hat doppeltes Interesse: einmal an sich selbst, dann aber auch als Controlversuch far die sich mit der Isolation der wirksamen Substanz der Nebennieren beschifftigten Experimente. Es erscheint unzweifelhaft, class die eigentlich wirksame Substanz der Nebennieren nur einen geringen Bruchtheil des Rohauszuges ausmacht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1926
1926
1935
1935

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ELLIOT (40) found that the capillaries of the nictitating membrane of the frog do not alter their calibre on local application of adrenaline while they are always contracted by stimulation of the sympathetic. MOORE and PURINTON (41) found that a very small dose of adrenaline causes (in Carnivora) diminution of blood-pressure, which is not observed as a result of weak sympathetic stimulation. BIEDL and REINER (42) observed adrenaline always to cause marked contraction of the cerebral vessels, which do not respond to stimulation of the sympathetic.…”
Section: Fifth Series Of Experiments Action Of Drugs Which Influencementioning
confidence: 99%
“…ELLIOT (40) found that the capillaries of the nictitating membrane of the frog do not alter their calibre on local application of adrenaline while they are always contracted by stimulation of the sympathetic. MOORE and PURINTON (41) found that a very small dose of adrenaline causes (in Carnivora) diminution of blood-pressure, which is not observed as a result of weak sympathetic stimulation. BIEDL and REINER (42) observed adrenaline always to cause marked contraction of the cerebral vessels, which do not respond to stimulation of the sympathetic.…”
Section: Fifth Series Of Experiments Action Of Drugs Which Influencementioning
confidence: 99%